The Factor of ELV Management System in Jerantut - Suhaimi, Ahmad Zulfatah; Raja Mamat, Tengku Nur Azila (Progress in Engineering Application and Technology, 2021)
Vehicles represent a main key of the today society and number of vehicles in use increases from year to year. However, whole life cycle of vehicles has a considerable impact on the environment. Whole life cycle of vehicles known as End-of-Life Vehicle. In Jerantut, many abandoned cars have been seen around the workshop in Jerantut. This study is intended to analyze the causes and factor of the abandoned cars management in Jerantut. Survey and interview have been released to the residents of Jerantut and workshop in Jerantut. Last but not least, in this study, the factor of the abandoned cars management can achieved the balance ELV management system in Jerantut.